Two-Photon Absorption and Multiphoton Excited Fluorescence of Acetamide-Chalcone Derivatives: The Role of Dimethylamine Group on the Nonlinear Optical and Photophysical Properties - André Gasparotto Pelosi; Eli Silveira-Alves; Leandro Henrique Zucolotto Cocca; João Victor Valverde; Guilherme Roberto Oliveira; Daniel Luiz da Silva; Leonardo De Boni; Pablo José Gonçalves; Cleber Renato Mendonca (Molecules, 2023)
This work studied the effect of different electron-withdrawing and electron-donating groups on the linear and nonlinear optical properties of acetamide-chalcone derivatives. The results showed that the addition of the dimethylamine group led to a large fluorescence emission (71% of fluorescence quantum yield in DMSO solution) that can be triggered by two and three-photon excitations, which is essential for biological applications. Furthermore, dimethylamine also red-shifts the lower energy state by approximately 90 nm, increasing the two-photon absorption cross-section of the lower energy band by more than 100% compared with the other studied compounds. All compounds presented two-electronic states observed through one and two-photon absorption spectroscopy and confirmed by Quantum Chemistry Calculations (QCCs). QCC results were also used to model the experimental two-photon absorption cross-sectional spectrum by the Sum-Over-States (SOS) approach, revealing a dependence between the coupling of the ground state with the first excited state and the transition dipole moment between these states.